أفكار فسيفساء الدعوة: دراسة عند دعوة سنن كالي جاغا - Batunnikmah, Khasib (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2019)
Making a unity of color components in every racial, ethnic, and ethnic, cultural and other differences in an area with the purpose of da’wa, that is the mosaic da’wa that a da'i will face and live on his journey especially in Indonesia. Every life form deserves live and develop, including ideas, perspectives, policies, attitudes and actions, by the people of a country towards something that is present and into the territory of certain regional communities. Multiculturalism began to be made an official policy in English-speaking countries (English-speaking countries), which began in Canada in 1971. In accommodating diverse community lives, the government then adopted the concept of cultural mosaics. This concept illustrates the diversity of ethnic groups living side by side in Canada where people can adapt themselves to differences in cultural ethnicity and the uniqueness of each culture. This gives different contrast spark plug to Canada. Cultural mosaics consist of three main categories: (a) demographic, (b) geographical, and (c) associative of cultural mosaics as in the times of Sunan Kaliogo in Indonesia at the time of da’wa at that time. Demographic variables related to race and ethnicity are most closely related to culture in general. Geographical variables refer to the physical features of an area. Associative Variables, forms and ways of social interaction that can enhance solidarity relations among humans. The collaborative effort to achieve a common goal that was applied by Wali Songo, namely the missionary goals and welfare of the Nusantara community in the 15th century 674 AD was equivalent to the mid 1470s.